2011
DOI: 10.1126/scitranslmed.3001845
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Receptor Deficiency Is Associated with a Major Reduction in Pro-Aging Signaling, Cancer, and Diabetes in Humans

Abstract: Life span extending mutations in growth signaling pathways protect against age-dependent DNA damage in yeast and decrease insulin resistance and cancer in mice. To test their effect in humans, we monitored for 22 years Ecuadorian subjects with mutations in the growth hormone receptor gene leading to severe growth hormone receptor (GHR) and IGF-I deficiencies and combined this information with surveys to identify the cause and age of death for subjects who died before this period. The individuals with GHR defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
519
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 662 publications
(553 citation statements)
references
References 79 publications
28
519
1
5
Order By: Relevance
“…In this regard, EL is associated with insulin sensitivity and insulin signaling (Willcox et al 2006;Barbieri et al 2008;Guevara-Aguirre et al 2011;Brunet 2012). Particularly, genetic variation in the insulin-FOXO3A gene pathway influences EL (Willcox et al 2008;Flachsbart et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, EL is associated with insulin sensitivity and insulin signaling (Willcox et al 2006;Barbieri et al 2008;Guevara-Aguirre et al 2011;Brunet 2012). Particularly, genetic variation in the insulin-FOXO3A gene pathway influences EL (Willcox et al 2008;Flachsbart et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the growth of the proximal tubules could be inhibited by LY294002 (Fig. 2 N and O) prompted us to investigate Insulin and Igf signaling, an evolutionarily conserved pathway regulating overall body and organ size (20,21,(28)(29)(30). Whereas Insulin and Igf receptors and the downstream signaling intermediate Irs1 were expressed throughout the embryo, two ligands, Insulin and Igf2 mRNAs, were specifically expressed in the proximal tubules of the kidney at stage 38 ( Fig.…”
Section: Significancementioning
confidence: 99%
“…In calorie-restricted individuals, when protein was reduced to maintenance levels and replaced isocalorically with other macronutrients, the level of insulin-like growth factor-1 (IGF-1) dropped substantially (Fontana et al 2008). This longevity marker, which is associated with cancer, diabetes, and dementia, including Alzheimer's disease (Paolisso et al 1997;Arai et al 2001;Carro et al 2002;Trejo et al 2002;Longo and Finch 2003;Pollak et al 2004;Carro and TorresAleman 2006;Fontana et al 2010;Guevara-Aguirre et al 2011;Duron et al 2012;Rajpathak et al 2012), is raised the least by lipids and most by protein consumption (Thissen et al 1994). A study of raw food enthusiasts consuming 40% of calories as lipid and a maintenance level of 0.7 g/kg of protein (Rand et al 2003),~10% of calories, showed similar low levels of IGF-I without apparent calorie restriction (Fontana et al 2008).…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%